Rancang Bangun Sistem Informasi Notulen Rapat : ( Studi Kasus : Fakultas Ilmu Komputer Universitas Lancang Kuning) - Lucky Lhaura Van FC; Lisnawita Lisnawita; Yogi Yunefri (ZONAsi: Jurnal Sistem Informasi, 2020)
Faculty of Computer Science of Universitas Lancang Kuning runs two departments, namely Informatics Engineering and Information System. The minute of meeting documentation, thus far, has been conducted manually in a ledger and written soon after the meeting. Consequently, when lecturer attendees wish to know the meeting results, they have to communicate with the meeting secretary. This method is inefficient; therefore, researchers have designed a web-based application to simplify the process. The proposing model is the waterfall technique, while PHP is used as the programming language. The system facilitates the attendance list and minutes of meetings created by the secretary and approved by the head of the meeting. This study's output is a web-based application to help faculties, particularly the academic, administration, studentship, and the cooperation units, regarding the minute of meetings' documentation process